Investigation of the 5-hydroxymethylfurfural and furfural content of Chinese traditional fermented vinegars from different regions and its correlation with the saccharide and amino acid content. (April 2020) - Gong, Min; Zhou, Zhilei; Yu, Yongjian; Liu, Shuangping; Zhu, Shenghu; Jian, Dongzhen; Cui, Pengjing; Zhong, Fang; Mao, Jian
Abstract: As an acidic system, Chinese traditional vinegar is rich in amino acids and sugars for the readily formation of 5-hydroxymethylfurfural (HMF) and furfural (F). The levels of HMF and F in Chinese vinegars from different regions were analyzed and discussed. F ranged from 4.35 to 313.95 mg/L, with an average value of 136.71 mg/L, while the mean level of HMF was 103.69 mg/L (26.83–455.13 mg/L). A significant positive correlation was observed between HMF and F, with a Pearson correlation (r) of 0.665. The relationships among the levels of HMF/F, free amino acids, sugars, and organic acids was investigated and evaluated by partial least squares regression (PLSR). HMF was significantly positively correlated with hexose, while F shared a significantly positive correlation with xylose, deoxyribose and sucrose. The results might help arouse concern about food safety of high HMF content and optimize different measures to ensure the quality in vinegar production. Highlights: The level of HMF and F in Chinese traditional vinegars were analyzed and discussed. Furfurals were high and varied widely in Chinese vinegars from different regions. A significant positive correlation was observed between the level of HMF and F. Correlation between HMF/F and physiochemical composition was modelled by PLSR. HMF and F were positively correlated with hexose and pentose, respectively.